Los tecnodioses de la transparencia: el voyerismo del Adán digitalis en la cibersociedad pornóptica (2021)
The ius-philosophical-theological dialectic, which is highlighted in this manuscript, is approached from four dimensions (quaestios): an anthropological dimension, from which man is presented as a human being that was gestated and developed in the channels of the rationality of Homo sapiens, but at present, aims to evolve and give rise to Homo digitalis. This idea allows the development of an ethical dimension, from which the main question that runs through the research is justified and that, specifically, seeks to investigate what is the idea of man that underlies and is built from the configuration of a Homo digitalis influenced by artificial intelligence (AI). In order to support the disputatio, a dimension of meaning is addressed, an issue from which man is presented as a construct that is exposed (from the dialectic of digital pornoptic), constantly supervised and imbued in the networks of AI, but his ‘virtual’ behavior leads him to the renunciation, almost involuntary, of certain freedoms and rights he presumes to dominate (and that breaks the scheme of a classic constitutionalism). Finally, as the last dimension, which would turn out to be holistic to the previous development, a synthesis of knowledge is exposed as an extended reason, by virtue of which a man with claims of technification is recognized who, at the same time, is objectified (voyeuristic) by the AI itself and seduced by the apple of virtuality which, in a vertiginous way, digests its human rationality.